Understanding users' continuance intention to use online library resources based on an extended expectation-confirmation model. Issue 4 (1st August 2016) - Joo, Soohyung; Choi, Namjoo
Abstract : Purpose: This study aims to investigate the factors affecting students' continuance intention to use online library resources (OLRs) in the context of academic libraries. Based on an extended expectation confirmation theory (ECT), the effects of usefulness, confirmation and resource quality on continuance intention to use OLRs were examined. Design/methodology/approach: To empirically test the model, a survey study was conducted. Data were collected from 606 student library users at a large state university in the USA. The collected data were analysed quantitatively to answer seven hypotheses using partial least squares method. Findings: The findings revealed that both usefulness and confirmation had a positive direct and indirect influence on continuance intention. Also, the effect of resource quality on continuance intention was found to be significant. Satisfaction had a mediating effect on the relationship between usefulness, confirmation and resource quality, and continuance intention. Originality/value: This study is one of the first attempts that adopted the ECT to understand students' continuance intention to use OLRs. In addition, the effect of the multiple dimensions of resource quality – accessibility, credibility, coverage, and format – on users' continuance intention to use OLRs was investigated.